A Clinical Study to Evaluate the Effect of Guduchyadi Rasayana as a Rasayana - Chauhan Bindu; Mishra Anjana; Chaudhary Vijay (International Journal of Ayurveda and Pharma Research, 2021)
Now a days reprehensive food habits, erroneous life style, stress, environmental pollution etc are exerting awful effects on human beings. Stress has become an inevitable and most unwanted companion of civilization. It can be induced by several factors like an environmental changes extremes of temperature, fear, anxiety, shock, grief, pain and so on. When the individual is unable to cope with it, it induces a number of clinical manifestations like hypertension, coronary artery disease, peptic ulcer, asthma, migraine, irritable bowel syndrome, fatigue, muscles pain, sleeping problem, behavioural disorders like anxiety and depression. Thus they are susceptible to develop premature aging and various disorders. Ayurvedic text describes Rasayana therapy to rejuvenate and nourish the body and mind. Ayurveda emphasizes on the importance of preventive medicine by boosting an individual’s own immune system. Rasayana therapy rejuvenates and prevents the effect of aging and improves the quality of life. Rasayana is useful in treating the disease as well as in maintaining the health of individuals. Rasayana drugs are having Balya, Medhya, Agnivardhaka, Ojovardhaka, Vyasthapna properties. It has been proved that these drugs are immunomodulator, adaptogenic, anti-stress, anti-anxiety and anti-depressant and hepatoprotective. So, Rasayana may be helpful to cope up with all the problems occurring due to modern lifestyle.